Casting Shadows: Analyzing 'Macbeth' through 'The Feminine Mystique” (ELATICS JOURNAL, 2023)
This study explores gender dynamics and the portrayal of women in William Shakespeare's "Macbeth" using Betty Friedan's "The Feminine Mystique" as a critical framework. Examining women's challenges in seeking power and agency within patriarchal societies, the analysis focuses on Lady Macbeth's character, emphasizing her ambition and defiance of traditional gender roles. The study also delves into the portrayal of witches in "Macbeth" to reveal insights into gender norms subversion and power dynamics. Applying the feminist lens of "The Feminine Mystique" unveils the witches' symbolic representation of women's agency and disruptive potential. The analysis underscores the enduring relevance of "Macbeth" and "The Feminine Mystique" in comprehending gender issues, inviting further exploration of gender representation in literature. By contributing to feminist literary criticism, this study enriches our understanding of gender dynamics in literary works, emphasizing the complexities women face when challenging societal expectations.